Gender-dependent relationship between metabolic syndrome and HOMA-IR index in patients with impaired fasting glucose - Ozkan Sevencan, Nurhayat; Ertinmaz Ozkan, Aysegul (Annals of Medical Research, 2021)
Aim: This study aimed to assess whether metabolic syndrome (MetS) criteria varied by gender and whether the homeostatic model assessment of insulin resistance (HOMA-IR) index could be used as a new MetS predictor. Materials and Methods: We performed a standard oral glucose tolerance test (OGTT) in 316 patients with impaired fasting glucose (IFG) and investigated the presence of impaired glucose tolerance (IGT), type 2 diabetes mellitus (T2DM), and MetS. Results: We found that MetS was higher in females than males. The obesity rate was 57.0% and 36.8% for females and males, respectively. Of the patients who reached stage 3 obesity,13.4% were females and 0.9% were males. The HOMA-IR score was not an independent predictor for MetS. However, sensitivity was 91% and specificity was 100% for the cut-off value of HOMA-IR ≥ 2.38 in diabetic females with MetS. Abdominal obesity (91.2%), hyperglycemia (81.5%), hypertension (71.8%), hypertriglyceridemia (62.0%), and low high-density lipoprotein (HDL) (57.8%) were found in MetS patients. Conclusion: Abdominal obesity and impaired glucose metabolism are powerful predictors demonstrating the presence of MetS. Females are at greater risk than males for obesity, T2DM, and MetS. Although the HOMA-IR score is not a new MetS predictor, it may be an effective indicator of the combination of MetS and diabetes in females.